2011
DOI: 10.4049/jimmunol.1003868
|View full text |Cite
|
Sign up to set email alerts
|

Natural but Not Inducible Regulatory T Cells Require TNF-α Signaling for In Vivo Function

Abstract: TNF-α has a multifunctional role in autoimmune diseases as reflected in the variable responses of different human diseases to anti–TNF-α therapy. Recent studies have suggested that TNF-α modulates autoimmunity partially via effects on regulatory T cells (Tregs) and that these effects are mediated through the type II TNFR (TNFR2). We have investigated the requirement for TNFR2-expression on murine natural Tregs (nTregs) and induced Tregs (iTregs) in mediating suppression of colitis. Surprisingly, we find that T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

10
77
1

Year Published

2013
2013
2020
2020

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 98 publications
(88 citation statements)
references
References 36 publications
(43 reference statements)
10
77
1
Order By: Relevance
“…[14][15][16]24 Our results extend, in an allo-HCT setting, the observation that Tconvs exert a powerful boost of Treg activity. We also demonstrate for the first time that the sole defect of TNF production by donor T cells was sufficient to completely abolish the Treg suppressive effect in GVHD.…”
Section: Discussionsupporting
confidence: 75%
“…[14][15][16]24 Our results extend, in an allo-HCT setting, the observation that Tconvs exert a powerful boost of Treg activity. We also demonstrate for the first time that the sole defect of TNF production by donor T cells was sufficient to completely abolish the Treg suppressive effect in GVHD.…”
Section: Discussionsupporting
confidence: 75%
“…There is some evidence that CD120b may mediate some of the pro-Treg functions of tumor necrosis factor-a. For example, tumor necrosis factor-a stimulates Treg proliferation through CD120b (30,31), CD120b signaling stabilizes Tregs in inflammatory environments (31), and expression of CD120b on Tregs is necessary for suppression of colitis (32). GARP is a receptor for latent transforming growth factor-b and can transfer the mature transforming growth factor-b to its receptor on the same cell or another target cell (33).…”
Section: Discussionmentioning
confidence: 99%
“…Dbc1 does not affect the development of nTreg cells, because the frequency and total number of thymic (24)(25)(26). The effect of the proinflammatory cytokine TNF-α on Treg cells remains controversial (28,29,(40)(41)(42). Grinberg-Bleyer et al (40) showed that TNF-α produced by T effector (Teff) cells boost Treg cells' expansion, whereas Valencia et al (28) reported that TNF-α down-modulated FOXP3 mRNA, FOXP3 protein, and their suppressive function.…”
Section: Discussionmentioning
confidence: 99%